Comparative assessment of the nature of the impact of ultraviolet radiation on watermelon seeds in time mode - A. V. Gulin; V. I. Donskaya (Овощи России, 2019)
Relevance. One of the main components of the spectrum of sunlight is ultraviolet rays – invisible to the human eye short-wave radiation. The influence of these rays on plant life was considered insignificant until recently, but recent studies have shown the fallacy of such conclusions. Ultraviolet has a beneficial effect not only on the human body and animals, but also on plants, including – crops. The destruction of the ozone layer is currently continuing under the influence of anthropogenic factors. In this regard, the study of the effect of ultraviolet radiation on living organisms, including plants, is very relevant from both theoretical and practical points of view. The epidermis of plant leaves and seed shells are permeable to medium-and long-wave UV radiation, so of particular interest is the ultraviolet radiation of the Sun and artificial sources of ultraviolet radiation in the range of 400...180 nm.Purpose of work: to assess the nature of the impact of ultraviolet radiation in the time mode on watermelon seeds using cytogenetic analysis.Methods. The material for research was the seeds of the watermelon variety "Astrakhan". The studies were conducted in 2017-2018.Results. The results of studies have shown that long-term exposure to ultraviolet radiation can affect the physiological processes and anatomical structure of plants, as well as have serious genetic changes: aneuploidy, cytotomy, pyknosis and various chromosomal aberrations that lead to mutations or death of plants. However, plants acquire useful mutations with short-term exposure-0.5-2 hours, which can be used later in selection.